Los criterios de eficiencia y el dilema del control en la cooperación internacional: análisis de los gobiernos locales en Andalucía - Huete García, Mª Ángeles (Revista Española de Desarrollo y Cooperación, 2023)
Using the technique of compared case studies, the article tries to explain why most of the Andalusian municipal cooperation is managed via NGO (what is called indirect management) and the pros and cons of such an approach.